1995
DOI: 10.1038/bjc.1995.389
|View full text |Cite
|
Sign up to set email alerts
|

Intra-arterial administration of the angiogenesis inhibitor TNP-470 blocks liver metastasis in a rabbit model

Abstract: Summary We evaluated the best route of administration of TNP-470, an angiogenesis inhibitor, by comparing the anti-tumour effects and toxicity following injection via the hepatic artery, the portal vein, or the jugular vein in a rabbit model of liver metastases. Following the injection of 1 x 106 VX2 carcinoma cells into the portal vein of rabbits, 50 mg of TNP-470 was injected continuously into the hepatic artery, portal vein, or jugular vein for 7 days. The number of tumours on the surface of the liver was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…TNP-470, a semisynthetic analogue of fumagillin isolated from Aspergillus fumigatus, is an anti-angiogenic agent. Recent studies have shown its anti-tumour or anti-metastatic activity in vivo and in vitro (Ingber et al, 1990;Kusaka et al, 1991; Yamanoto et al, 1994;Tanaka et al, 1995). Interestingly, some reports have also indicated a correlation between angiogenesis and lymph node metastasis (Bosari et al, 1992;Guidi et al, 1994).…”
mentioning
confidence: 99%
“…TNP-470, a semisynthetic analogue of fumagillin isolated from Aspergillus fumigatus, is an anti-angiogenic agent. Recent studies have shown its anti-tumour or anti-metastatic activity in vivo and in vitro (Ingber et al, 1990;Kusaka et al, 1991; Yamanoto et al, 1994;Tanaka et al, 1995). Interestingly, some reports have also indicated a correlation between angiogenesis and lymph node metastasis (Bosari et al, 1992;Guidi et al, 1994).…”
mentioning
confidence: 99%
“…Daily and intermittent injection of TNP-470 produces anti-tumour effects against various tumours in mice (Ingber et al, 1990), and it has also been reported that TNP-470 was able to prevent micrometastasis by suppression of angiogenesis (Tanaka et al, 1995a and b;Konno et al, 1996). Tanaka et al (1995a) have reported that intra-arterial administration of TNP-470 blocked liver metastasis formation more effectively than intraportal or systemic administration in a rabbit model.…”
Section: Discussionmentioning
confidence: 99%
“…12) The angiogenesis inhibitor TNP-470, a semisynthetic analogue of fumagillin produced by Aspergillus fumigatus, has been demonstrated to suppress the growth and metastasis of various tumors including sarcoma, melanoma, lung cancer and colon cancer of mouse, rat or human origin [13][14][15][16][17][18][19][20] by the selective inhibition of vascular endothelial cell proliferation. 21,22) In the present study, in order to demonstrate the suppressive effect of TNP-470 on the development of primary hepatic nodules, we performed a morphometric analysis of chemical carcinogen-induced hepatic nodules in rats treated with or without TNP-470, with special reference to the difference in the effectiveness of TNP-470 among non-arterialized HPN, arterialized HPN, AHPN and HCC.…”
Section: Abstract: Tnp-470 -Hepatocarcinogenesis -Angiogenesis -Capimentioning
confidence: 99%
“…10) In murine hepatic nodules as well, arterialization proceeds with the advance of stages of hepatocarcinogenesis from HPN to HCC. 10) In parallel with the progress of arterialization and stages, the microvasculature of hepatic nodules undergoes sequential ultrastructural changes from sinusoids to capillaries.8, 11) Non-arterialized HPN show the normal features of hepatic sinusoids, while arterialized HPN and AHPN exhibit transitional figures from sinusoids to capillaries, and HCCs usually have typical capillaries.Recently, various kinds of angiogenesis inhibitors have been developed for the purpose of preventing hematogenous tumor metastases by interfering with angiogenesis, which is critical for the growth of tumors.12) The angiogenesis inhibitor TNP-470, a semisynthetic analogue of fumagillin produced by Aspergillus fumigatus, has been demonstrated to suppress the growth and metastasis of various tumors including sarcoma, melanoma, lung cancer and colon cancer of mouse, rat or human origin [13][14][15][16][17][18][19][20] by the selective inhibition of vascular endothelial cell proliferation. 21,22) In the present study, in order to demonstrate the suppressive effect of TNP-470 on the development of primary hepatic nodules, we performed a morphometric analysis of chemical carcinogen-induced hepatic nodules in rats treated with or without TNP-470, with special reference to the difference in the effectiveness of TNP-470 among non-arterialized HPN, arterialized HPN, AHPN and HCC.…”
mentioning
confidence: 99%